MDSCs use a complex molecular network to suppress T-cell immunity in a pulmonary model of fungal infection - Kaminski, Valéria Lima; Borges, Bruno Montanari; Santos, Bianca Vieira; Preite, Nycolas Willian; Calich, Vera Lucia Garcia; Loures, Flávio Vieira (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Paracoccidioidomycosis (PCM) is a systemic endemic fungal disease prevalent in Latin America. Previous studies revealed that host immunity against PCM is tightly regulated by several suppressive mechanisms mediated by tolerogenic plasmacytoid dendritic cells, the enzyme 2,3 indoleamine dioxygenase (IDO-1), regulatory T-cells (Tregs), and through the recruitment and activation of myeloid-derived suppressor cells (MDSCs). We have recently shown that Dectin-1, TLR2, and TLR4 signaling influence the IDO-1-mediated suppression caused by MDSCs. However, the contribution of these receptors in the production of important immunosuppressive molecules used by MDSCs has not yet been explored in pulmonary PCM. Methods: We evaluated the expression of PD-L1, IL-10, as well as nitrotyrosine by MDSCs after anti-Dectin-1, anti-TLR2, and anti-TLR4 antibody treatment followed by P. brasiliensis yeasts challenge in vitro. We also investigated the influence of PD-L1, IL-10, and nitrotyrosine in the suppressive activity of lung-infiltrating MDSCs of C57BL/6-WT, Dectin-1KO, TLR2KO, and TLR4KO mice after in vivo fungal infection. The suppressive activity of MDSCs was evaluated in cocultures of isolated MDSCs with activated T cells. Results: A reduced expression of IL-10 and nitrotyrosine was observed after in vitro anti-Dectin-1 treatment of MDSCs challenged with fungal cells. This finding was further confirmed in vitro and in vivo by using Dectin-1KO mice. Furthermore, MDSCs derived from Dectin-1KO mice showed a significantly reduced immunosuppressive activity on the proliferation of CD4+ and CD8+ T lymphocytes. Blocking of TLR2 and TLR4 by mAbs and using MDSCs from TLR2KO and TLR4KO mice also reduced the production of suppressive molecules induced by fungal challenge. In vitro, MDSCs from TLR4KO mice presented a reduced suppressive capacity over the proliferation of CD4+ T cells. Conclusion: We showed that the pathogen recognition receptors (PRRs) Dectin-1, TLR2, and TLR4 contribute to the suppressive activity of MDSCs by inducing the expression of several immunosuppressive molecules such as PD-L1, IL-10, and nitrotyrosine. This is the first demonstration of a complex network of PRRs signaling in the induction of several suppressive molecules by MDSCs and its contribution to the immunosuppressive mechanisms that control immunity and severity of pulmonary PCM.